2010
DOI: 10.1061/(asce)em.1943-7889.0000187
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wireless Smart Sensor Performance

Abstract: The Newmark Structural Engineering Laboratory (NSEL) of the Department of Civil and Environmental Engineering at the University of Illinois at Urbana-Champaign has a long history of excellence in research and education that has contributed greatly to the state-of-the-art in civil engineering. Completed in 1967 and extended in 1971, the structural testing area of the laboratory has a versatile strong-floor/wall and a three-story clear height that can be used to carry out a wide range of tests of building materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Over the past several years, the CSE domains gradually have targeted the implementation of analytical methods to detect and quantify structural damage by using reliable sensing technologies [Farrar and Worden 2012;Linderman et al 2010;Rice and Spencer 2009;Bocca et al 2011;Whelan and Hietbrink 2012;Peckens and Lynch 2013;Araujo et al 2012]. While WSNs are gradually receiving attention from the CSE as an attractive tool, many engineering applications (e.g., SHM) are receiving attention from the computer science domain.…”
Section: Existing Wns-based Shm Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past several years, the CSE domains gradually have targeted the implementation of analytical methods to detect and quantify structural damage by using reliable sensing technologies [Farrar and Worden 2012;Linderman et al 2010;Rice and Spencer 2009;Bocca et al 2011;Whelan and Hietbrink 2012;Peckens and Lynch 2013;Araujo et al 2012]. While WSNs are gradually receiving attention from the CSE as an attractive tool, many engineering applications (e.g., SHM) are receiving attention from the computer science domain.…”
Section: Existing Wns-based Shm Approachesmentioning
confidence: 99%
“…-Irregular sensing field. There is the irregular sensing field constraint, for example, not a square or circle shape on a building, aircraft, or other structure [Linderman et al 2010]. -Location.…”
Section: C4 (Location Assignment Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data loss in wireless communication has been reported by several researchers for various applications [3], [4], [5], [6], [7], [8]. Nagayama [9], in particular, has analyzed the influence of data loss on structural and modal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…• In controlled experimentation with the Imote / CC2420 radio Rice [15] demonstrated that the use of an external, omnidirectional antenna (the Antenova Titanis) had a significant effect in terms of Received Signal Strength in an anechoic chamber when compared to an integrated/on board antenna. Subsequent field tests examining line of sight transmission ranges demonstrated that this antenna was capable of transmitting around 3 times the distance of the on-board chip antenna (300 m compared to 100 m).…”
Section: Literature Reviewmentioning
confidence: 99%